2023
DOI: 10.1159/000530134
|View full text |Cite
|
Sign up to set email alerts
|

Definitive Liver Radiotherapy for Intrahepatic Cholangiocarcinoma with Extrahepatic Metastases

Abstract: Introduction: Tumor-related liver failure (TRLF) is the most common cause of death in patients with intrahepatic cholangiocarcinoma (ICC). Though we previously showed that liver radiotherapy (L-RT) for locally advanced ICC is associated with less frequent TRLF and longer overall survival (OS), the role of L-RT for patients with extrahepatic metastatic disease (M1) remains undefined. We sought to compare outcomes for M1 ICC patients treated with and without L-RT. Methods: We reviewed ICC patients found to have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…The MST in our registry is 21.7 months, which seems to be a good result compared to chemotherapy alone, but these data do not include cases with active distant metastases and the conditions were good even among unresectable ICC cases. De et al [43] have recently described the advantages of radiotherapy for ICC with metastases. In a comparison of chemotherapy alone with radiotherapy, 82% of deaths with chemotherapy alone were found to be caused by liver recurrence, but after radiotherapy this rate dropped to 47%, with distant metastasis becoming the leading cause of death [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MST in our registry is 21.7 months, which seems to be a good result compared to chemotherapy alone, but these data do not include cases with active distant metastases and the conditions were good even among unresectable ICC cases. De et al [43] have recently described the advantages of radiotherapy for ICC with metastases. In a comparison of chemotherapy alone with radiotherapy, 82% of deaths with chemotherapy alone were found to be caused by liver recurrence, but after radiotherapy this rate dropped to 47%, with distant metastasis becoming the leading cause of death [43].…”
Section: Discussionmentioning
confidence: 99%
“…De et al [43] have recently described the advantages of radiotherapy for ICC with metastases. In a comparison of chemotherapy alone with radiotherapy, 82% of deaths with chemotherapy alone were found to be caused by liver recurrence, but after radiotherapy this rate dropped to 47%, with distant metastasis becoming the leading cause of death [43]. It was concluded that radiotherapy is associated with a lower rate of death caused by liver recurrence and with longer survival [43].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, among patients with M1 iCCA, similar to those with locally advanced unresectable disease, a majority of patients die of complications of tumor-related liver failure. For M1 iCCA patients, delivering ablative-dose radiotherapy to achieve LC of the dominant liver disease was found to be associated with prolonged OS compared with a parallel cohort of patients treated with chemotherapy alone as well as with a matched cohort from the National Cancer Database 55 . Notably, patients with M1 iCCA who received radiotherapy in this series were less likely to die of tumor-related liver failure than those who received systemic therapy alone, but those in the radiotherapy group were more likely to die of extrahepatic disease progression eventually.…”
Section: Escalated Dose Radiotherapy For Iccamentioning
confidence: 97%
“…A series of studies have demonstrated that in the era of gemcitabine/cisplatin, hepatic vascular compromise and biliary obstruction constitute the cause of death in the vast majority of patients with iCCA 53–55 . For example, in a retrospective study of 362 patients with unresectable iCCA, local tumor progression caused liver failure in 89% of patients 56 .…”
Section: The Critical Need To Achieve Local Control For Iccamentioning
confidence: 99%
See 1 more Smart Citation